Diagnostic Ability and Capacity of Optical Coherence Tomography-Angiography to Detect Retinal and Vascular Changes in Patients with Fibromyalgia. (27th August 2022) - Garcia-Martin, Elena; Tello, Alvaro; Vilades, Elisa; Perez-Velilla, Javier; Cordon, Beatriz; Fernandez-Velasco, Diego; Garcia-Campayo, Javier; Puebla-Guedea, Marta; Satue, Maria
Abstract : Background . To evaluate the neuroretina and retinal vasculature of fibromyalgia (FM) patients and calculate a linear discriminant function (LDF) to improve retinal parameters' contribution to FM diagnosis. Methods . Fifty FM patients and 232 healthy controls underwent retinal evaluation using swept-source optical coherence tomography (SS-OCT) angiography (Triton plus; Topcon) and spectral domain OCT (SD-OCT) (Spectralis; Heidelberg). The macular (m) and peripapillary (p) retinal nerve fibre layer (RNFL) and ganglion cell layer (GCL) were assessed, as was the macular vascular density. A logistic regression analysis was performed, and an LDF was calculated to evaluate OCT's contribution to FM diagnosis. Results . With Triton OCT, the patients presented pRNFL thinning in the temporal sector (p = 0.006 ). Spectralis OCT measurements showed decreased pRNFL in patients in the following sectors: superonasal, p = 0.001 ; nasal, p = 0.001 ; inferonasal, p = 0.006 ; temporal, p = 0.001 ; and inferotemporal, p = 0.001 . No significant differences were observed in the macular vascular plexus between patients and controls. However, vascular density in the superior sector showed a strong inverse correlation with disease duration ( r = −0.978, p = 0.022 ). The LDF calculated for Spectralis OCT yielded an area under the ROC curve of 0.968. Conclusions . FM patients present RNFL thinning observable using SS- and SD-OCT. However, these patients show similar vascular density in the macular area to healthy controls. The LDF that combines several RNFL parameters obtained using Spectralis OCT gives this device a powerful ability to differentiate between healthy individuals and individuals with FM.